Book publishing activity of scientific and educational institutions in the Republic of Tyva: modern problems - M. S. Oorzhak (Библиосфера, 2016)
This article examines modern trends of the educational and scientific publishing development in the Republic of Tyva. The author uses statistics and unpublished sources provided information on the activity of largest centers in the scientific and educational publishing fields in the republic.